2009
DOI: 10.1055/s-0028-1103295
|View full text |Cite
|
Sign up to set email alerts
|

Rivastigmine Reduces Tobacco Craving in Alcohol-dependent Smokers

Abstract: Our preliminary data indicate an effect of rivastigmine on tobacco craving and consumption. This pilot study encourages further investigation of acetylcholinesterase-inhibitors as a promising treatment approach regarding tobacco dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Although, our study did not assess smoking behavior, several studies support the potential effectiveness of AChE inhibitors for smoking cessation. In a 12-week clinical trial for the treatment of alcohol addiction that included 26 alcoholic smokers, rivastigmine treatment of 6 mg/day reduced the number of cigarettes smoked, the amount of exhaled carbon monoxide (CO) and the craving for cigarettes (Diehl et al 2009). In another clinical trial for alcohol dependence, GAL treatment reduced smoking behaviors, including cigarettes used per day, as well as cotinine levels in 114 alcohol-dependent smokers (Diehl et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, our study did not assess smoking behavior, several studies support the potential effectiveness of AChE inhibitors for smoking cessation. In a 12-week clinical trial for the treatment of alcohol addiction that included 26 alcoholic smokers, rivastigmine treatment of 6 mg/day reduced the number of cigarettes smoked, the amount of exhaled carbon monoxide (CO) and the craving for cigarettes (Diehl et al 2009). In another clinical trial for alcohol dependence, GAL treatment reduced smoking behaviors, including cigarettes used per day, as well as cotinine levels in 114 alcohol-dependent smokers (Diehl et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulating evidence from clinical studies supports the potential efficacy of AChE inhibitors for the treatment of nicotine dependence. For example, in alcohol-dependent smokers, rivastigmine (Diehl et al 2009) or GAL (Diehl et al 2006) treatment was associated with reduced smoking behavior without providing any specific behavioral treatments for cigarette smoking. In spite of this limitation, these studies support the potential use of AChE inhibitors for the treatment of nicotine addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Galantamine has some beneficial effects on cognition and drug use in stimulant abusers (Sofuoglu and Carroll, 2011; Sofuoglu and Mooney, 2009; Sofuoglu et al, 2011) and may improve inhibitory control in abstinent smokers (Sofuoglu et al, 2012). Preliminary studies with cholinesterase inhibitors in alcoholic, methamphetamine-dependent, and schizophrenic smokers show that they are well tolerated but provide mixed results for efficacy with respect to reducing smoking behavior (De la Garza and Yoon, 2011; Diehl et al, 2006; Diehl et al, 2009; Kelly et al, 2008). …”
Section: Implications For Treatment Developmentmentioning
confidence: 99%
“…In fact, the acetylcholinesterase (AChE) inhibitor galantamine reduced smoking and craving for cigarettes in alcohol-dependent participants (Diehl et al 2006), although similar effects were not observed in smokers with schizophrenia (Kelly et al 2008). More recently, 4 weeks of the AChE and butyrylcholinesterase (BuChE) inhibitor rivastigmine (6 mg/day) produced significant decreases in both smoking and craving relative to placebo in alcohol-dependent participants (Diehl et al 2009). To our knowledge there are no data on the effects of AChE inhibitors on smoking behaviors in healthy, non-drug-dependent individuals.…”
Section: Introductionmentioning
confidence: 99%